The reciprocal relationships between meaning in life and smartphone addiction among Chinese college students: evidence from a three-wave cross-lagged panel model - Hao Zhao; Hao Zhao; Tianjiao Song; Tianjiao Song; Shameem Rafik-Galea; Jihe Dong; Mimi Fitriana; Yanhong Ji; Jianling Zhang (Frontiers Media S.A., 2023)
BackgroundPrevious cross-sectional studies have shown that meaning in life (MIL) is closely associated with college students' smartphone addiction (SA), but the causal relationship between MIL and college students' SA is uncertain. Therefore, conducting a longitudinal study to explore their relationship is very necessary. Furthermore, some studies have implied possible gender differences in the relationship between MIL and SA and the relationship between SA and MIL. Therefore, it is necessary to further examine whether there are gender differences in the above relationships.MethodsThe present study constructed a three-wave cross-lag panel model to explore the relationships between MIL and college students' SA. Three waves of data were collected from 705 college students (male: 338; female: 367) in China for three consecutive years, and the interval of data collection was 1 year. These college students completed the same online questionnaire regarding MIL and SA.Results(1) The MIL of male college students was significantly stronger than that of female college students at time 1, time 2, and time 3, (2) Female college students' SA at time 1, time 2, and time 3 was more serious than that of male college students, (3) There were reciprocal relationships between MIL and college students' SA, (4) The influence of MIL on female college students' SA was significantly stronger than that of male college students, and (5) The influence of SA on female college students' MIL was significantly stronger than that of male college students.ConclusionThis study showed reciprocal relationships between MIL and SA among male college students and female college students. The findings further deepen our understanding of the relationship between MIL and SA and provide a gender perspective for preventing or intervening with college students' SA.